Leela and the lost shoe: oxford literacy web - Morgan, Michaela; Newsham, Ian (Oxford University Press Hong kong, 2000)
Fitting the requirements of the National Literacy Strategy, National Curriculum in England and Wales, English Language 5-14 in Scotland, and Common Curriculum in Northern Ireland, this book guides pupils through the core skills associated with learning to read and write with a diverse range of literary styles.